Ready or Not to Adopt a Pedagogy of Play for Children Starting School in Scottish Primary Schools-Is this a Major Transition for Teachers? - Burns, Marion (International Journal of Educational and Life Transitions, 2022)
By drawing on empirical data, this article will question how ready Scottish primary teachers are to adopt a pedagogy of play as opposed to more traditional didactic teaching approaches when planning and delivering an early years curriculum for children starting school. Children transitioning to school have traditionally been expected to be ‘school ready’; preparing them for a culture where play has yet to be consistently and universally embraced as pedagogy. The author draws on the results of a small-scale qualitative study which explored the multiple realities of ensuring curriculum continuity and progression in children’s learning between the early learning and childcare sector and primary school sector in Scotland.The study demonstrated that realising a play-based curriculum while consistent with pedagogical practice in the two early learning and childcare settings was not yet common practice in the three Primary 1 classes. Furthermore, children experienced two early years curriculum traditions: the nursery curriculum tradition and the Primary 1 curriculum tradition. Each tradition is rooted in the different sociocultural norms and structures which exist in the early learning and childcare sector and in the early stages of primary schools in Scotland. Children starting school needed to adjust how they learned in readiness for the Primary 1 curriculum tradition.The implications for policy makers and others include empowering teachers to embrace playful pedagogy through cross sectoral collaboration so that children starting school can benefit from a continuous play-based curriculum experience. Future research could explore contested understandings of school readiness that persist, influencing curriculum content and pedagogical approaches nationally and internationally.
Keywords: didactic teaching; early years curriculum; play pedagogy; school readiness; transition to school